Training Parent-Country Professionals in Host-Country Organizations - Pazy, Asya; Zeira, Yoram (Academy of Management Review, 1983)
This paper introduces an innovative training method for professionals employed by parent organizations and trained in host organizations. The method is presented as a unique combination of on-the-job and off-the-job training that draws on the strengths of the two. The advantages and the limitations of the program for the parent and the host organizations are described in terms of the learning of the individual professional, the relationships between the two systems, and the internal processes within each system.